Crystal Structure of Refolding Fusion Core of Lassa Virus GP2 and Design of Lassa Virus Fusion Inhibitors - Zhang, Xuejiao; Wang, Cong; Chen, Baohua; Wang, Qian; Xu, Wei; Ye, Sheng; Jiang, Shibo; Zhu, Yun; Zhang, Rongguang (Frontiers in Microbiology, 2019)
The envelope glycoproteins GP1 and GP2 of Lassa virus (LASV) bind to the host cell receptors to mediate viral infection. So far, no approved vaccines and specific treatment options against LASV exist. To develop specific fusion inhibitors against LASV, we solved the crystal structure of the post-fusion 6 helix bundle (6-HB) formed by two heptad repeat domains (HR1 and HR2) of GP2. This fusion core contains a parallel trimeric coiled-coil of three HR1 helices, around which three HR2 helices are entwined in an antiparallel manner. Various hydrophobic and charged interactions form between HR1 and HR2 domains to stabilize the overall conformation of GP2 fusion core. Based on the structure, we designed several peptides spanning the HR2 domain and tested their antiviral activities. We found that the longer HR2 peptides were effective in inhibiting LASV GPC protein-mediated cell–cell fusion under low pH condition. These results not only suggest that LASV infects the target cell mainly through endocytosis, including micropinocytosis, and membrane fusion at low pH, but also provide an important basis for rational design of LASV fusion inhibitors.